Evaluación de las cuentas por cobrar del Gad Municipal del Cuerpo de Bombero de Jujan del periodo 2022 - 2023. - Cornejo Higuera, Jampier Oswaldo (2023)
The purpose of this study is to examine the accounts receivable of the Jujan Fire Department, through an analysis with the financial information of the year 2022 to September 2023, this study found findings, in which problems were recorded in the accounts receivable and This affects the liquidity of the company, since its debts depend on it, therefore, profitability decreases. Likewise, you may not have enough money to pay your employees. Despite the problems identified, according to the liquidity indicator, the company was able to cover its financial obligations. This study is useful because it helps us understand how a high value in accounts receivable affects your liquidity and solvency, and in turn limits your investment and affects other parts of the company.